2020
DOI: 10.1186/s13059-020-01974-9
|View full text |Cite
|
Sign up to set email alerts
|

Ultraplexing: increasing the efficiency of long-read sequencing for hybrid assembly with k-mer-based multiplexing

Abstract: Hybrid genome assembly has emerged as an important technique in bacterial genomics, but cost and labor requirements limit large-scale application. We present Ultraplexing, a method to improve per-sample sequencing cost and hands-on time of Nanopore sequencing for hybrid assembly by at least 50% compared to molecular barcoding while maintaining high assembly quality. Ultraplexing requires the availability of Illumina data and uses inter-sample genetic variability to assign reads to isolates, which obviates the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…Recently, Dilthey et al postulated a new method that allows the multiplexing step to be skipped by pooling together multiple non-barcoded samples in the same ONT flow cell [ 17 ]. This method relies on the availability of Illumina data and inter-sample genetic differences to in silico assign ONT reads to particular isolates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Dilthey et al postulated a new method that allows the multiplexing step to be skipped by pooling together multiple non-barcoded samples in the same ONT flow cell [ 17 ]. This method relies on the availability of Illumina data and inter-sample genetic differences to in silico assign ONT reads to particular isolates.…”
Section: Discussionmentioning
confidence: 99%
“…There are different strategies to decrease the price of completing a genome with ONT sequencing [ 16 , 17 ]. Recently, Lipworth et al [ 18 ] showed that use of wash-kits coupled with shorter sequencing times can be optimized to obtain 36 complete genomes per single flow cell, achieving a reduction in long-read sequencing costs of 27%.…”
Section: Introductionmentioning
confidence: 99%
“…Evaluation of minimap2 was performed analogously to HiLive2's, selecting the representative alignment if a chimeric match was found. In addition to the simulated data prepared as explained above, we also used two real SRA datasets: a SARS-CoV-2 isolate (SRR11140745, collected on 14 Feb 2020) and a clinical S. aureus sample (SRR8776887 [40]).…”
Section: Real Illumina Runsmentioning
confidence: 99%
“…Even with ultra-short run times of 12 h (1/6th of the total run time that is currently standard in our laboratory and others) we were able to circularize the vast majority of plasmids (and most chromosomes). Combining washing steps with a recently published chemistry-free approach to demultiplexing may provide additional savings and would seem worth exploring in future work [18]. Whilst we had access to a large university computer cluster, this will not be the case for all investigators, though we estimate that if one were to use cloud computing (e.g.…”
Section: Discussionmentioning
confidence: 99%